The Perception of Output Users for the Quality of Services for Procurement of Goods and Services in the Brawijaya University Environment - Shofi Saiful Haqqi; Unti Ludigdo; Choirul Saleh (Wacana Journal of Social and Humanity Studies, 2021)
This research has the objective to find out the quality of services perceived by users of the services for goods and services procurement as provided by the Office of Procurement Services of Brawijaya University, with the Public Satisfaction Index for principles of service. The research utilized the descriptive research method with the qualitative approach because it is desired to be able to describe and reveal user satisfaction in the process of goods and services procurement in the environment of Brawijaya University. This research was conducted at the Rectorate, Faculties, and Goods and Services Procurement Institution Unit of Brawijaya University. The data analysis in this research consisted of three stages: open coding, axial coding, and selective coding. The results of this research indicated five important points of service quality, which are Tangibles, Reliability, Responsiveness, Assurance, and Empathy, for the Procurement Institution Unit of Brawijaya University. From the five dimensions of service quality, it can be concluded that users have not been satisfied with the provided services that they obtained. Services for goods and services procurement have not yet proceeded according to the needs and desires of users, and therefore the matter requires special attention from the staff of goods and services procurement to improve service quality so that the provided services can proceed well according to the desires and expectations of students. This would then be mutually beneficial for both parties.